Colorimetric Examination of Typical Free Flap Donor Sites and Comparison to Recipient Sites in the Extremities - Ensat, Florian; Greindl, Markus; Skreiner, Anna; Schubert, Heinrich; Hladik, Michaela; Stuflesser, Alexander; Spies, Marcus; Wechselberger, Gottfried (Journal of Reconstructive Microsurgery, 2013)
Results after free flap reconstruction in the extremities are often impaired by missing color match of the transferred flap and the recipient site. But pre-existing color match is the precondition for satisfying aesthetic results. To obtain suitable free flap donor sites in terms of color for extremity reconstruction and to understand frequent color mismatch, we performed a colorimetric study including 60 healthy volunteers. Ten free flap donor sites were compared with ten recipient sites in the extremities. The results of our study showed that lower extremity sites are markedly lighter than upper extremity sites with the exception of the palmar forearm. We encountered an excellent color match of the radial forearm flap to the back of the hand (4.10 ± 1.91) and the palm of the hand (5.62 ± 2.21), and significantly relevant color match to the palmar aspect of the forearm (2.52 ± 1.23). Additionally, the lateral arm flap showed a remarkable color match to the dorsal aspect of the forearm (3.13 ± 2.06). Furthermore we encountered significantly relevant color match of the fibula flap to the anterior aspect of the lower leg (2.01 ± 1.08) and excellent color match of the anterolateral thigh flap (ALT) to the palmar aspect of the forearm (3.66 ± 2.10). No further significantly relevant color differences between the other donor sites and recipient regions were found. Colorimetric measurements are a helpful tool in reconstructive surgery to compare skin color of different anatomic sites.
Keywords: colorimetry; skin color; extremity reconstruction